Movimentos sociais e políticas educacionais na Era da barbárie - Novaes, Henrique Tahan (Editora Oficina Universitária, 2020)
The chapters that make up the book entitled Social movements and educational policies in the era of barbarism, organized by Henrique Tahan Novaes, present results of different researches carried out in doctoral, masters and scientific initiation works, which have as their unifying theme work, education and democracy in social movements. The main category that permeates the different studies is that of associated work. Associated work concerns collectives of workers who self-organize to produce. In the self-organization of the workers, new work relationships and the division of power are experienced, which point to an organizational perspective of anti-hegemonic work. In addition to work organization, another recurring theme in associated work collectives is education, theorized and practiced as an education beyond capital. Contact with this excellent book will undoubtedly provide a very useful reading for people interested in themes related to democratic education and associated work.